Information retrieval : 8th Russian Summer School, RuSSIR 2014, Nizhniy, Novgorod, Russia, August 18-22, 2014, Revised selected papers /: 8th Russian Summer School, RuSSIR 2014, Nizhniy, Novgorod, Russia, August 18-22, 2014, Revised selected papers. (2015) - Unknown
No abstract available